PEMBERDAYAAN UMKM MELALUI PELATIHAN PEMBUKUAN SEDERHANA UNTUK MENINGKATKAN PENGELOLAAN KEUANGAN PELAKU USAHA UMKM MINYAK VCO BALI NIRMALA DI DESA KESIMAN KERTALANGU - Komang Ayu Siska Lestari; Ni Ketut Muliati; utu Ayu Diana Gita Maharani,; Ni Luh Putu Widya Yanti; Ni Kadek Dewi Harnika Putri (Dharma Bhakti, 2023)
In this era, the business world is developing very rapidly and requires high creativity in facing changes from economic actors. Kesiman Kertalangu Village is a village located in East Denpasar District, Denpasar City which consists of 11 hamlets. Apart from having many tourist attractions with beautiful views, Kesiman Kertalangu Village also has MSMEs that use natural products to be processed as health products. Bali Nirmala VCO Oil UMKM processes coconut using Usadha Bali fermentation technology. The Bali Nirmala VCO Oil UMKM has not implemented bookkeeping effectively and combined money from business with personal income so that it cannot know the exact amount of profit obtained from its business. In community service activities through this village project program, UNHI Accounting students help overcome this problem by providing simple bookkeeping training to improve the financial management of Bali Nirmala VCO Oil MSME business actors so that in the future the business can thrive and further increase its income through good financial management.